Intravenous golimumab is effective in patients with active rheumatoid arthritis despite methotrexate therapy with responses as early as week 2: results of the phase 3, randomised, multicentre, double-blind, placebo-controlled GO-FURTHER trial. Issue 3 (1st June 2012) - Weinblatt, Michael E; Bingham, Clifton O; Mendelsohn, Alan M; Kim, Lilianne; Mack, Michael; Lu, Jiandong; Baker, Daniel; Westhovens, Rene
Abstract : Objectives: Evaluate the efficacy of intravenous golimumab 2 mg/kg+methotrexate (MTX) in patients with active rheumatoid arthritis (RA) receiving MTX. Methods: Patients (n=592) with active disease (≥6/66 swollen, ≥6/68 tender joints, C-reactive protein ≥1.0 mg/dl, rheumatoid factor positive and/or anticyclic citrullinated protein antibody positive at screening) despite MTX (15–25 mg/week) participated in this double-blind, placebo-controlled, phase 3 study. Patients were randomised (2:1) to receive intravenous golimumab 2 mg/kg, or placebo infusions at weeks 0 and 4 and every (q) 8 weeks; patients continued MTX. Placebo patients with <10% improvement in combined swollen/tender joint counts at week 16 could early escape to intravenous golimumab 2 mg/kg. The primary endpoint was week 14 American College of Rheumatology 20% (ACR20) response. Analyses employed non-responder imputation and last-observation-carried-forward. Results: At week 14, significantly (p<0.001) larger proportions of golimumab+MTX than placebo+MTX patients achieved ACR20 response (59% vs 25%, respectively), a disease activity score of good/moderate (EULAR) response (81% vs 40%), and greater median improvement in health assessment questionnaire scores (0.500 vs 0.125). Improvements versus placebo+MTX were observed by week 2. Similar proportions of patients receiving golimumab+MTX and placebo+MTX, respectively, reported adverse events through week 16 (47% and 44%) and week 24 (53% and 49%). Serious adverse events were reported by more golimumab+MTX (4.1%) than placebo+MTX (2%) patients at week 24. Conclusion: The addition of intravenous golimumab rapidly and significantly improved signs and symptoms in patients with active RA despite ongoing MTX, in some patients by week 2.